Enrichment of milk with magnesium provides healthier and safer dairy products. (December 2017) - Ben-Ishay, Noa; Oknin, Hilla; Steinberg, Doron; Berkovich, Zipi; Reifen, Ram; Shemesh, Moshe
Abstract Biofilms on the surfaces of milk-processing equipment are often a major source of contamination of dairy products. Members of the genusBacillus appear to be among the most commonly found bacteria in dairy farms and processing plants.Bacillus species may thrive in dairy farm equipment and in dairy products since they can form robust biofilms during growth within milk. We found that fortification of milk with magnesium mitigated biofilm formation byBacillus species, and thus could notably reduce dairy product spoilage. We also show that the mode of action of Mg2+ ions is specific to inhibition of transcription of genes involved in biofilm formation. Our further findings indicate that in the presence of Mg2+ bacterial cells are hypersensitive to the heat pasteurization applied during milk processing. Additionally, we demonstrated that enrichment of milk with magnesium improved technological properties of milk products such as soft cheeses. Finally, we report that there is a notable increase in the intestinal bioavailability potential of magnesium from supplemented milk compared with that from non-supplemented milk.